PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA KARYAWAN PT PENERBIT PUSTAKA MULIA SEJAHTERA JAKARTA TIMUR - Muhamad Fajar; Endang Susilo Wardani (Accounting UNIPA - Jurnal Akuntansi, 2025)
This research aims to analyze the influence of job satisfaction and work stress on employees' intention to leave (turnover intention) at PT Publisher Pustaka Mulia Sejahtera, East Jakarta. This research sample involves permanent employees. The data collection method uses a questionnaire, while data analysis uses multiple linear regression. According to Handoko (in Sutrisno, 2019) argues that job satisfaction is a pleasant or unpleasant emotional state for employees who view their work, according to Ghofur & Irwanto, (2019) where work stress can appear at any time in someone when they feel in a good position that is emphasized in work or instructions given by superiors which can result in decreased performance, according to Lum et al. in Khotimah (2020) turnover intention is an individual's desire and revolves around the current position based on dissatisfaction to influence someone when leaving and finding work outside the company. The results of this research show a t value of 0.264 < t table 2.776 and a significance of 0.736 > 0.01 so that partially there is a positive and significant influence between job satisfaction on Turnover Intention and a correlation coefficient test value of 0.862. And the results of this research show a positive and significant influence between the Job Stress variable on Turnover Intention. Based on the table, t count is 0.264 < t table 2.776 and is significant 0.793 < 0.01 so that partially there is a positive and significant influence of work stress on Turnover Intention.  The F test result is 82.744 and the significant value is 0.000. So it can be concluded that job satisfaction and work stress simultaneously have a significant effect on Turnover Intention, as evidenced by the Fcount value of 82.744 > Ftable 2.76 and the significant value of 0.000 < 0.01. So the decision H0 can be drawn. rejected Ha accepted. And the results of the Coefficient of Determination test are 0.744 or 74.4%, so it can be concluded that the variables of job satisfaction and work stress on Turnover Intention have an effect of 74.4%, the remaining 25.6% is influenced by other factors outside this research.